Plants, Rituals, and Cultural Heritage: Indigenous Knowledge Systems of the Jirel Community in Dolakha District - Ghimire, Anuska; Devkota, Balak (Educational Journal, 2025)
Nepalese indigenous communities have long integrated plant in ritual and ceremonial purposes reflecting deep-rooted traditions and belief systems. Hence, this study was conducted to explore the plants use in cultural and religious performs of the Jirel tribe of Dolakha district, Bagmati province, Nepal. This study employed ethnographic case study method under qualitative research design. The study employed purposive sampling strategy and identified five key informants possessing in-depth ethnobiological knowledge. Data collection was conducted using semi-structured and open-ended questionnaires and field observation. The data was analyzed by using qualitative thematic approach. The findings indicate that twelve species were identified used by the Jirels in their birth rites and five species in wedding rites. Jirel worships showed strong bonding with the plants resource utilization, have socio-ecological value, symbolic meanings and spiritual values. The research has triggered the need for conservation of such indigenous knowledge by establishing knowledge transfer systems in the offsprings.